Inflammatory Bowel Disease Patients Are at Increased Risk of Invasive Pneumococcal Disease: A Nationwide Danish Cohort Study 1977–2013. (November 2015) - Kantsø, Bjørn; Simonsen, Jacob; Hoffmann, Steen; Valentiner‐Branth, Palle; Petersen, Andreas Munk; Jess, Tine
Abstract : OBJECTIVES: Inflammatory bowel disease (IBD), Crohn's disease (CD), and ulcerative colitis (UC) are chronic diseases characterized by an inappropriate immune response, which may also increase the risk of infections. We investigated the risk of invasive pneumococcal disease (IPD) before and after diagnosis of IBD in a population‐based cohort study. METHODS: In a cohort of 74, 156 IBD patients and 1, 482, 363 non‐IBD controls included and followed during 1977–2013, hazard rate ratios (HRs) for IPD in IBD patients vs. controls were calculated by Cox regression. Within the IBD group, we also calculated the risk according to ever use of specific IBD medications. Next, using conditional logistic regression, we evaluated the odds of IPD prior to IBD diagnosis. RESULTS: The HRs for IPD within the first 6 months after IBD diagnosis were significantly and more than threefold increased and then decreased to a constant level, which for CD was significantly increased (approximately twofold, HR, 1.99; 95% confidence interval (CI), 1.59–2.49) and for UC non‐significantly just above 1. IBD medication use including tumor necrosis factor alpha antagonists had limited impact on the risk of IPD, although having ever used azathioprine increased the risk of IPD in patients with UC (HR, 2.38; 95% CI, 1.00–5.67). Up to 4 years prior to IBD diagnosis, the odds ratio for IPD was significantly increased (UC HR, 1.51, 95% CI, 1.05–2.17; CD HR, 1.79, 95% CI, 1.05–3.03). CONCLUSIONS: The risk of IPD is significantly increased both before and after diagnosis of IBD, with limited impact of IBD medications. This suggests that the risk of IPD in patients with IBD is related to the underlying altered immune response in these patients.